Evolution of water-soluble and water-insoluble portions in the solid products from fast pyrolysis of amorphous cellulose - Liu, D.; Yu, Yun; Wu, Hongwei (American Chemical Society, 2013)
The formation of water-soluble intermediates is an important phenomenon during cellulose pyrolysis. This study investigates the evolution of the water-soluble and water-insoluble portions in the solid products during the pyrolysis of an amorphous cellulose sample, which is known to generate substantial amounts of water-soluble intermediates at low temperatures (250 and 300 °C). The yield of the water-soluble portion initially increases to a maximum up to 30% (on a carbon basis), depending on the pyrolysis conditions used in this study. Further pyrolysis reactions lead to a decrease in the yield of the water-soluble portion. In contrast, the yield of the water-insoluble portion initially decreases rapidly as pyrolysis proceeds and then starts to level off. Such leveling-off behavior of the water-insoluble portion indicates that at least part of the water-soluble portion is converted into the water-insoluble portion through repolymerization. An increase in temperature promotes the formation of the water-soluble portion because of the rapid breakage of hydrogen bonds in the pyrolyzing cellulose. The formation of non-sugar structures is accompanied by the evolution of the water-soluble and water-insoluble portions during pyrolysis. At the same conversion level, a higher temperature also results in the formation of more non-sugar structures in the water-soluble portion but fewer non-sugar structures in the water-insoluble portion. Because of the structural changes in both the water-soluble and water-insoluble portions, the selectivities of high-DP anhydro-sugar oligomers in the water-soluble portion decrease as pyrolysis proceeds. Higher temperature promotes the formation of anhydro-sugar oligomers, but reduces the selectivities of low-DP anhydro-sugar oligomers.